Pyrazol-3-yldiazonium Salts as Key Reagents for C–C Bond Formation and Pyrazole-Containing Heterocycle Synthesis - Barabash, Oksana V.; Ostapiuk, Mary Y.; Kravets, Mykola; Obushak, Mykola D.; Schmidt, Andreas; Ostapiuk, Yurii V. (Synthesis, 2025)
A novel application of 1-methylpyrazol-3-yldiazonium salts in the Meerwein reaction was introduced. These diazonium salts reacted with α,β-unsaturated functionalized compounds under Meerwein reaction conditions to yield pyrazole-containing building blocks, which subsequently allowed cyclization reactions with bisnucleophiles for the synthesis of pyrazol-3-yl-containing heterocyclic systems. In this way, pyrazole-containing heterocyclic compounds with 2-aminothiazole, 2-aminoselenazole, thiazolidin-4-one, selenazolidin-4-one, 3-hydroxythiophene, and 3-aminothiophene rings were efficiently prepared.
Keywords: 3-aminopyrazoles; pyrazolyldiazonium salts; Meerwein reaction; thiazoles; selenazoles; thiophenes; C–C bond formation